2022
DOI: 10.21833/ijaas.2022.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Level of perceived stress and coping styles through positive mental health among nursing students in Hail, Saudi Arabia

Abstract: This study aims to determine the level of stress and the coping style through positive mental health status among student nurses. Further, it aimed to look into the relationship between the level of stress and positive mental health. The study was conducted at the University of Hail, College of Nursing using the descriptive cross-sectional approach. Data was gathered in three months from November to January 2020 through a self-administered questionnaire. There were 175 student nurses who participated in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(34 reference statements)
0
0
0
Order By: Relevance
“…The study revealed that psychiatric education nurses exhibited a modest level of resilience, as shown by their mean score, prior to the implementation of the intervention. However, following the completion of the program, these nurses demonstrated a significantly higher mean score in resilience and with Albaqawi and Sanat Alrashidi's (2022) [24] study, who employed a quantitative-comparative correlational research approach, utilizing a self-administered questionnaire to collect data from a sample of 393 nurses in the Hail Region, Saudi Arabia. The distribution of adapted questionnaires was conducted via a Google Form survey.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The study revealed that psychiatric education nurses exhibited a modest level of resilience, as shown by their mean score, prior to the implementation of the intervention. However, following the completion of the program, these nurses demonstrated a significantly higher mean score in resilience and with Albaqawi and Sanat Alrashidi's (2022) [24] study, who employed a quantitative-comparative correlational research approach, utilizing a self-administered questionnaire to collect data from a sample of 393 nurses in the Hail Region, Saudi Arabia. The distribution of adapted questionnaires was conducted via a Google Form survey.…”
Section: Discussionmentioning
confidence: 80%
“…The development of programs aimed at enhancing or cultivating resilience among nurse educators is of utmost importance for schools of nursing. The provision of support and training in the field of online education is of utmost significance, also, to Albaqawi and Sanat Alrashidi (2022) [24] study, who revealed a statistically significant association between gender and moral resilience (p < .25).…”
Section: Discussionmentioning
confidence: 88%